Decreased Antibiotic Susceptibility in Pseudomonas aeruginosa Surviving UV Irradition - Li, Hai-bei; Hou, Ai-ming; Chen, Tian-jiao; Yang, Dong; Chen, Zheng-shan; Shen, Zhi-qiang; Qiu, Zhi-gang; Yin, Jing; Yang, Zhong-wei; Shi, Dan-yang; Wang, Hua-ran; Li, Jun-wen; et al. (Frontiers in Microbiology, 2021)
Given its excellent performance against the pathogens, UV disinfection has been applied broadly in different fields. However, only limited studies have comprehensively investigated the response of bacteria surviving UV irradiation to the environmental antibiotic stress. Here, we investigated the antibiotic susceptibility of Pseudomonas aeruginosa suffering from the UV irradiation. Our results revealed that UV exposure may decrease the susceptibility to tetracycline, ciprofloxacin, and polymyxin B in the survival P. aeruginosa. Mechanistically, UV exposure causes oxidative stress in P. aeruginosa and consequently induces dysregulation of genes contributed to the related antibiotic resistance genes. These results revealed that the insufficient ultraviolet radiation dose may result in the decreased antibiotic susceptibility in the pathogens, thus posing potential threats to the environment and human health.